Sterilization Study: Vasectomy and Tubectomy - Risnawati Ramli; Nur Ainun Basry; Maryanti Fidmatan; Israyani; Jusriyani (Newinera Publisher, 2020)
Birth planning for a couple from the first and subsequent births can be arranged so that the welfare of the community increases and other undesirable things can be anticipated from afar. The methods include using contraception or prevention of pregnancy and family planning. Sterilization is to spay a man or woman by operating (in general) so as not to produce offspring. Sterilization for men (vasectomy) and women (tubectomy). Procedurally, vasectomy in men is relatively simpler than tubectomy while the procedure for tubectomy is a bit complicated and complex.